Effect of oxytocin on in vitro prostaglandin production and expression of PGFS and PGES mRNAs in buffalo corpus luteum - TRIPATHI, M K; MONDAL, S; MOR, A; REDDY, I J (The Indian Journal of Animal Sciences, 2018)
The present study investigated the effect of various doses of oxytocin on in vitro PGF2α and PGE2 production and expression profiling of PGFS and PGES mRNA in buffalo CL. Buffalo ovaries with mid-luteal phase CL were collected from the abattoir and CL was separated from surrounding tissues, chopped, rinsed with HBSS medium supplemented with gentamicin and BSA and incubated at 37°C for 1 h in HBSS containing collagenase. The cell suspension following filtration was treated with increasing doses of oxytocin (1, 10, 102, 103 and 104 ng/ml) and cultured at 38.5ºC, 5% CO2 level for 24 h. The production of PGF2α and PGE2 were not significantly different among different treatment groups as compared to control. The expression of PGES and PGFS mRNAs were not significantly different among different treatment groups as compared to control. It can be concluded that oxytocin may not directly stimulate PGF2α and PGE2 production in mid-luteal stage buffalo corpus luteum.